Legal aspects of ensuring the competitivenss of the shipping companies in Ukraine - Vorkunova, O.; Hoteeva, N. (Економічні інновації, 2012)
The article deals with the normative base of the maritime traffic, including the national legislation, international contracts and Merchant marine code of Ukraine that is the necessary element of insuring the competitiveness of the shipping companies in Ukraine.